Gender Differences in Face-to-Face Deceptive Behavior - Tim Lohse; Salmai Qari (Center for Economic Studies and ifo Institute (CESifo), 2019)
We study the role of face-to-face interaction for gender differences in deceptive behavior and perceived honesty. In the first part, we compare women's to men's deceptive behavior using data from an incentivized income reporting experiment in which lies can be detected in the course of an audit. Between the three treatments of that experiment, (i) the degree, and (ii) the impact of the face-to-face interaction vary from none (computerized baseline treatment) to a little (treatment in which face-to-face communication triggers psychological effects such as greater lying aversion) to much (treatment in which the perception by others also enters as a strategic effect determining the probability of detecting a lie). In the computerized baseline treatment men and women lie alike. Women's truthfulness increases when psychological effects of face-to-face interaction come into play. In contrast, male deceptive behavior does not change until the strategic effect of perceived honesty matters and men's truthfulness rises way beyond the level of women. To elaborate on these gender differences, in the second part, participants are asked to assess the honesty of videotaped statements from an experimental setting identical to the third treatment. We find that more men are assessed as rather dishonest. Men's dishonest perception is independent of whether they are actually truthful or not and whether they are assessed by men or women. We conclude that men anticipate their low perceived honesty in a face-to-face setting and, therefore, deceive less compared to women.
Keywords: C91; D91; J16; 330; gender differences; lying; face-to-face interaction; honesty assessment; perception; video analysis; laboratory experiment